Cesium, strontium and sodium diffusion in magnesium kalium phosphates system - Dikiy, N.P.; Dovbnya, A.N.; Lyashko, Yu.V.; Medvedev, D.V.; Medvedeva, E.P.; Repikhov, O.A.; Saenko, S.Y.; Shkuropatenko, V.A.; Tarasov, R.V.; Fedorets, I.D.; Khlapova, N.P. (Вопросы атомной науки и техники, 2014)
Nuclear-physical methods have been used for determination of diffusion coefficient of Cs, Na, Sr and Ga in samples on the basis of Ceramicrete which contained simulators of a liquid radioactive waste of "Hanford-1", KW and KE Basin sludge, 10% wollastonite and 0.3% of boric acid. After an irradiation of investigated samples by electrons and brake radiation to a dose 100 and 1 MGy, accordingly, leaching was conducted at temperature 37°C. Values of diffusion coefficient of Cs, Sr, Na changed in process of leaching from units of 10⁻¹⁰ cm²/s till 10⁻¹⁶ ... 10⁻¹⁷ cm²/s, for Ga - from units of 10⁻¹³ cm²/s to 10⁻¹⁶ cm²/s. Decreasing of weight of ceramics in process of leaching during 858 hours irradiated by electrons to a dose 100 MGy, on 14.6 and 18.5% with simulators KE and KW is revealed, accordingly. Decreasing of weight of ceramics in process of leaching during 858 hours, irradiated brake radiation to a dose 1 MGy, on 19.9 and 21.6% with simulators KW and KE, accordingly is revealed. The sums of relations of diffusion coefficient of Na concerning Cs and Sr are in antagonistic dependence on the Cs and Sr content in a matrix on the basis of Ceramicrete. Ядерно-физические методы были использованы для определения коэффициентов диффузии Cs, Na, Sr и Ga в образцах на основе керамики Ceramicrete, которые содержали имитаторы жидких радиоактивных отходов "Хенфорд-1", KW и KE Basin sludge, 10% волластонита и 0.3% борной кислоты. После облучения исследуемых образцов электронами и тормозным излучением до дозы 100 и 1 МГр, соответственно, было проведено выщелачивание при температуре 37°C. Значения коэффициентов диффузии цезия, стронция, натрия изменялись в процессе выщелачивания от единиц 10⁻¹⁰ см²/с до 10⁻¹⁶ ... 10⁻¹⁷ см²/с, для галлия от единиц 10⁻¹³ см²/с до 10⁻¹⁶ см²/с. Обнаружено уменьшение веса керамики в процессе выщелачивания в течение 858 часов, облученных электронами до дозы 100 МГp, на 14,6 и 18,5% с имитаторами KE и KW, соответственно. Обнаружено уменьшение веса керамики в процессе выщелачивания в течение 858 часа, облученной гамма-квантами до дозы 1 МГp, на 19,9 и 21,6% с имитаторами KW и KE, соответственно. Обнаружено, что суммы отношений коэффициента диффузии натрия относительно цезия и стронция находятся в антагонистической зависимости от содержания цезия и стронция в матрице на основе Ceramicrete. Ядерно-фiзичнi методи були використанi для визначення коефiцiєнтiв дифузiї Cs, Na, Sr i Ga в зразках на основi керамiки Ceramicrete, якi мiстили iмiтатори рiдких радiоактивних вiдходiв "Хенфорд-1", KW i KE Basin sludge, 10 % волластонiтy i 0.3% борної кислоти. Пiсля опромiнення дослiджуваних зразкiв електронами i гальмiвним випромiнюванням до дози 100 i 1 МГр, вiдповiдно, було проведено вилуговування при температурi 37°C. Значення коефiцiєнтiв дифузiї цезiю, стронцiю, натрiю змiнювалися в процесi вилуговування вiд одиниць 10⁻¹⁰ см²/с до 10⁻¹⁶ ... 10⁻¹⁷ см²/с, для галiю вiд одиниць 10⁻¹³ см²/с до 10⁻¹⁶ см²/с. Виявлено зменшення ваги керамiки в процесi вилуговування протягом 858 годин, опромiнених електронами до дози 100 МГp, на 14,6 i 18,5% з iмiтаторами KE i KW, вiдповiдно. Виявлено зменшення ваги керамiки в процесi вилуговування протягом 858 години, опромiненої гама-квантами до дози 1 МГp, на 19,9 i 21,6% з iмiтаторами KW i KE, вiдповiдно. Виявлено, що суми вiдносин коефiцiєнта дифузiї натрiю до цезiю та стронцiю знаходяться в антагонiстичної залежностi вiд вмiсту цезiю та стронцiю в матрицi на основi Ceramicrete.